2016
DOI: 10.1111/jwas.12395
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Quantitative Real‐time Polymerase Chain Reaction Assay for the Detection of Aeromonas salmonicida

Abstract: A rapid, economical, specific, and sensitive quantitative real‐time polymerase chain reaction (qPCR) assay coupled with SYBR Green I chemistry was developed for the quantitative detection of Aeromonas salmonicida from farmed Atlantic salmon, Salmo salar, with the symptoms of furunculosis. The set of primers designed from the virulence array protein (vapA) gene was specific to A. salmonicida. Compared with the conventional PCR, qPCR had a lower detection limit of 5.6 copies of the positive plasmids. The standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…For example, Hiney et al (1992) reported a polymerase chain reaction (PCR) that was capable of detecting ~ 2 cells of A. salmonicida, whereas Høie et al (1997) detected 10 3 and 10 4 colony forming units (CFUs) of A. salmonicida in 100 ml of kidney suspension with 16S rRNA sequencing and plasmid primers, respectively. Subsequent developments included nested PCR (Taylor and Winton 2002), terminal-restriction fragment length polymorphism (RFLP) (Nilsson and Strom 2002), PCR-RFLP (Puah et al 2018), multiplex PCR (Chapela et al 2018), real-time PCR (Keeling et al 2013), quantitative real-time-PCR (Du et al 2017), real-time recombinase polymerase amplification (Pang et al 2019) and reverse transcription-multiplex PCR (Rattanachaikunsopon and Phumkhachorn 2012). All these techniques reported extremely high levels of sensitivity, detecting numbers of cells well below the level associated with occurrences of clinical disease (Austin and Austin 2016).…”
Section: Culture-independent Methods-molecular Biologymentioning
confidence: 99%
“…For example, Hiney et al (1992) reported a polymerase chain reaction (PCR) that was capable of detecting ~ 2 cells of A. salmonicida, whereas Høie et al (1997) detected 10 3 and 10 4 colony forming units (CFUs) of A. salmonicida in 100 ml of kidney suspension with 16S rRNA sequencing and plasmid primers, respectively. Subsequent developments included nested PCR (Taylor and Winton 2002), terminal-restriction fragment length polymorphism (RFLP) (Nilsson and Strom 2002), PCR-RFLP (Puah et al 2018), multiplex PCR (Chapela et al 2018), real-time PCR (Keeling et al 2013), quantitative real-time-PCR (Du et al 2017), real-time recombinase polymerase amplification (Pang et al 2019) and reverse transcription-multiplex PCR (Rattanachaikunsopon and Phumkhachorn 2012). All these techniques reported extremely high levels of sensitivity, detecting numbers of cells well below the level associated with occurrences of clinical disease (Austin and Austin 2016).…”
Section: Culture-independent Methods-molecular Biologymentioning
confidence: 99%
“…The positive results on type V and type VI spiked water samples support the potential use of the molecular assays for monitoring purposes in hatchery sites. In general, Aeromonas salmonicida isolation from environmental samples has been attempted on solid medium cultivation methods in the past with not encouraging results (Du et al., 2017; Teska & Cipriano, 1993). The bacterium is difficult to recover from these samples where mixed bacterial communities co‐exist due to the lack of selective media and overgrowth of concomitant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In many quantitative analysis of pathogens, the detection of pathogens relied upon plate cultivation (Farto et al., ; Kashulin & Sorum, ; Liu et al., ). Compared with this traditional method, qPCR used here was rapid, economical, specific and sensitive for the quantitative detection of AS‐C4, with just a detection limit of 5.6 copies of one PCR reaction (Du, Liu, et al., ). AS‐C4 was detected in almost all tissue samples of fish from the bath test.…”
Section: Discussionmentioning
confidence: 99%
“…| 1827 (N = 4) were also sampled according the above protocols and all samples were kept at À80°C for genomic DNA extraction. A new qPCR assay was designed to detect the copy numbers of A. salmonicida in different tissues of Atlantic salmon in our laboratory (Du, Liu, et al, 2016). The design of primers in this new qPCR system was based on the virulence array protein (vapA) gene of A. salmonicida (GenBank accession no.…”
Section: Bath Challenge and Samplingmentioning
confidence: 99%
See 1 more Smart Citation